2021
DOI: 10.1017/s0033291721000817
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tDCS during inhibitory control training on performance and PTSD, aggression and anxiety symptoms: a randomized-controlled trial in a military sample

Abstract: Background Post-traumatic stress disorder (PTSD), anxiety, and impulsive aggression are linked to transdiagnostic neurocognitive deficits. This includes impaired inhibitory control over inappropriate responses. Prior studies showed that inhibitory control can be improved by modulating the right inferior frontal gyrus (IFG) with transcranial direct current stimulation (tDCS) in combination with inhibitory control training. However, its clinical potential remains unclear. We therefore aimed to replicate a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 71 publications
0
37
0
Order By: Relevance
“…Similar findings were shown during an intrusive memory suppression task with trauma-exposed civilians, where PTSD- individuals showed reduced IFG-parahippocampal functional connectivity but not PTSD+ individuals, supporting a potential disruption of the regulation signal that helps to control activation of unwanted memories in individuals with PTSD (Mary et al, 2020 ). Importantly, there is evidence that rIFG activation and connectivity with other fear-related brain regions can improve with trauma-focused treatment (Rousseau et al, 2019 ) and may improve emotion and fear regulation when targeted using transcranial direct current stimulation (tDCS) (Herrmann, Beier, Simons, & Polak, 2016 ), although findings are mixed (Smits, Geuze, Schutter, van Honk, & Gladwin, 2021 ). A recent resilience model of PTSD has been suggested whereby post-trauma biomarkers of cognitive control, specifically dorsolateral PFC structural integrity, promotes resilience (Roeckner, Oliver, Lebois, van Rooij, & Stevens, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were shown during an intrusive memory suppression task with trauma-exposed civilians, where PTSD- individuals showed reduced IFG-parahippocampal functional connectivity but not PTSD+ individuals, supporting a potential disruption of the regulation signal that helps to control activation of unwanted memories in individuals with PTSD (Mary et al, 2020 ). Importantly, there is evidence that rIFG activation and connectivity with other fear-related brain regions can improve with trauma-focused treatment (Rousseau et al, 2019 ) and may improve emotion and fear regulation when targeted using transcranial direct current stimulation (tDCS) (Herrmann, Beier, Simons, & Polak, 2016 ), although findings are mixed (Smits, Geuze, Schutter, van Honk, & Gladwin, 2021 ). A recent resilience model of PTSD has been suggested whereby post-trauma biomarkers of cognitive control, specifically dorsolateral PFC structural integrity, promotes resilience (Roeckner, Oliver, Lebois, van Rooij, & Stevens, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Detailed evaluation of the risk of bias is reported in Supplementary Table 1. The majority of studies were considered at high risk of bias, both for the studies included for primary outcome analysis ( studies applied and reported appropriate randomization (48,50,52,57,63,66). Overall, according to the GRADE guidelines (39), evidence from this study was considered of moderate quality.…”
Section: Risk Of Bias In Methodologymentioning
confidence: 99%
“…First despite performing an extensive search of literature databases and applying PRISMA recommendations, a limited number of studies were included, with relatively small sample sizes [except for two studies measuring disorder-specific symptoms; (63,66)]. Second, the primary outcome of the meta-analysis (generic anxiety scales results) was the explicit primary outcome in only 5/19 of the studies included.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, many studies have enrolled male participants only, making it impossible to investigate potential gender effects [88,90,94,96]. Further methodological limitations concern the single tDCS sessions and absence of follow-up measures [30,33,39,41,46,48,52,88]; indeed, given that the literature focuses on the acute effects of the stimulation (i.e., immediately after the stimulation), no evidence is available for the long-term effects.…”
Section: Limitsandfutureper S Pec Tive Smentioning
confidence: 99%
“…Smits et al [90] found a null effect of tDCS on aggressiveness. Authors recruited a military sample with PTSD or impulsive aggression and performed a‐tDCS stimulation over the right Inferior Frontal Gyrus (IFG) coupled with inhibitory control training.…”
Section: Aggressiveness Impulsivity Clinical Conditions and Tdcsmentioning
confidence: 99%